Failure rates of class V restorations in the management of root caries in adults – a systematic review. (14th November 2014) - Hayes, Martina; Brady, Paul; Burke, Francis M.; Allen, P. Finbarr
Abstract : Objective: The aim of this systematic review was to compare cumulative failure rates of different restorative materials in carious class V lesions on the root surfaces of adult patients. Background: The prevalence of root caries is set to increase in the coming years as a result of ageing of the population and a concomitant reduction in levels of edentulousness. Evidence is needed to assist practitioners to select the most appropriate restorative material for use in these lesions. Methods: A search of the literature was undertaken using the electronic databases of PubMed, Embase, CENTRAL and OpenSIGLE using keywords relevant to the search question. Two review authors conducted the electronic search independently, and any conflict was resolved by discussion. The references quoted in the full text articles extracted were hand searched for any further eligible studies. Results: Sixty non‐duplicate citations were screened. Following review of the titles, abstracts, texts and application of the pre‐determined inclusion/exclusion criteria, five studies remained. Conclusion: There is a need for more research in this area as many of the studies identified in this systematic review treated post‐radiation, xerostomic patients which are not typical of the general population. Increased adherence to CONSORT guidelines for reporting is also advised to facilitate future systematic review and meta‐analysis in this area.